Supercritical carbon dioxide extraction of astaxanthin from Paracoccus NBRC 101723: Mathematical modelling study. Issue 13 (1st September 2016) - Chougle, Jyoti A.; Bankar, Sandip B.; Chavan, Prakash V.; Patravale, Vandana B.; Singhal, Rekha S.
ABSTRACT: Astaxanthin (AX) is a secondary metabolite that accumulates inside the cell during Paracoccus fermentation. The fermentation biomass was extracted using supercritical carbon dioxide (SC-CO2 ). The solubility parameter of AX, CO2 and entrainer solvents was calculated and validated with experimental results. The pressure and particle size of the biomass had a significant effect on the extraction of AX. A maximum recovery of 963.33 μg/g of AX was obtained after SC-CO2 extraction at 40ºC, 350 bar and a run time of 60 min with ethanol (20% v/w) as an entrainer. Further, the experimental data has been modelled using non-linear regression analysis method.